Design and Experimental Research of a New Shaped Charge Liner for Enhanced Armor Piercing and Lateral Damage - Peng Zhou; Rujiang Li; Dan Zhou; Tiansheng Liu; Mengfei Wang; Zhenyu Wang (Shock and Vibration)
This study investigates the enhancement of lateral damage effects after armor penetration by utilizing grooved shaped-charge liners. Traditional methods often fail to achieve penetration and damage comparable to copper warheads when engaging distant targets or targets with interlayer materials. By modifying the liner structure, the jet can be redirected off-axis after penetrating the target, improving the overall damage effectiveness. Smooth Particle Hydrodynamics (SPH) simulations were employed to model the fragment cloud damage effects of high-velocity metal jets from internally grooved liners, and comparisons were made with nongrooved liners. The results show that the fragment clouds generated by grooved liners exhibit greater dispersion angles and velocities than those from nongrooved liners, with groove spacing positively correlated with the divergence angle. SPH simulations align with experimental data, demonstrating that groove spacing and depth significantly influence the primary and secondary perforation areas. Overall, the grooved liner design significantly enhances lateral damage effects, and the consistency between experimental and simulation data further validates its effectiveness. The findings provide new insights and references for improving the postpenetration damage design of shaped-charge warheads.